PERAN PEMERINTAH DAERAH DALAM PENGEMBANGAN DESA WISATA KABUPATEN BANDUNG - Dino Gustav Leonandry Maskarto Lucky Nara Rosmadi (JI@P, 2018)
Leonandry & Rosmadi, 2018. “The Role Of Local Governments In TheDevelopment Of The Tourist Village Of Bandung RegencyKeywords: Quality Of Service”. STP Trisakti Jakarta, STIE KridatamaBandung.Tourist village is one of the supporting and supporting factors in improvingpeople's welfare. Potentials owned by the village culture, natural beauty,and creative industries be used as capital to increase people's income.One of the tourism in Bandung Regency is Mekarsari village, PasirjambuSubdistrict. Mekarsari tourism village is unlikely to develop without theattention of various parties including local government. The purpose ofthis research is to know how far the role of local government in supportingMekarsari tourism village destination. The research method used isdescriptive analytical with qualitative approach. Data collection techniquesconsist of primary data obtained from respondents and secondary data inthe form of literature, scientific journals both nationally and internationally.From the results of research conducted obtained the results thatmekarsari tourism village to grow and develop with the support ofsurrounding communities in an effort to improve welfare. The role of thegovernment and the banking world is less contributing in developing thevillage of Mekarsari as a tourist village.Keywords: Village Tourism, Cisondari Village, Local government.